Effectiveness of Nutritional Advice for Community-Dwelling Obese Older Adults With Frailty: A Systematic Review and Meta-Analysis - Yin, Yue-Heng; Liu, Justina Yat Wa; Fan, Tsz Man; Leung, Kit Man; Ng, Man Wai; Tsang, Tsun Yee; Wong, Ka Po; Välimäki, Maritta (Frontiers in Nutrition, 2021)
Objectives: This systematic review was aimed to examine the effectiveness of nutritional advise interventions compared with usual care, or exercise, or exercise combined with nutritional advice as a means of improving the body weight, body composition, physical function, and psychosocial well-being of frail, obese older adults. Methods: CINAHL, Cochrane Library, Embase, MEDLINE, PsycINFO, and Scopus databases were searched to identify relevant studies. The quality of the included studies was assessed using Cochrane's risk of bias tool 2. Meta-analysis was performed with respect to body weight and fat mass. Other outcomes were synthesized narratively. Results: Eight articles (from two studies) with a total of 137 participants were included in the review. The results revealed that nutritional advice was more effective than exercise in reducing body weight and fat mass. The nutritional advice was also beneficial in enhancing physical function and psychosocial well-being. However, it was less effective than exercise or combined interventions in increasing muscle strength and preventing lean mass loss. Conclusions: Nutritional advice is an essential intervention for reducing body weight and fat mass, for enhancing physical function, and for improving the psychosocial well-being of obese older adults experiencing frailty. The limited number of studies included in this review suggests that there is a need for more well-designed interventional studies in order to confirm these findings.